The Impact of ATM Services on Customer Satisfaction of Nepalese Commercial Banks - Awasthi, Puja (Nepalese Journal of Finance, 2025)
This study examines the impact of ATM services on customer satisfaction in Nepalese commercial banks. Customer satisfaction is the dependent variable. The selected independent variables are tangible, reliability, responsiveness, assurance, and price charged. The primary source of data is used to assess the opinions of respondents regarding tangible, reliability, responsiveness, assurance, price charged, and customer satisfaction. The study is based on primary data of 129 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the impact of ATM services on customer satisfaction in Nepalese commercial banks. The study showed a positive impact of tangibility on customer satisfaction. It indicates that ease of locating the ATM like visibility, accessibility etc. influenced the level of satisfaction of customers. Similarly, the study showed a positive impact of reliability on customer satisfaction. It indicates that higher the reliability of ATM service provided by banks influences the level of customer satisfaction. Likewise, the study also revealed a positive impact of responsiveness on customer satisfaction. It indicates that being able to react quickly leads to an increase in customer satisfaction. Further, the study observed a positive impact of assurance on customer satisfaction. It indicates that customers get influenced by the assurance of ATM service provided by banks that lead to increase in customer satisfaction. In addition, the study observed a positive impact of price charged on customer satisfaction. It indicates that fairly charged prices on ATMs lead to an increase in customer satisfaction.